TAMAN REKREASI PANTAI PASARBANGGI DENGAN PENDEKATAN ARSITEKTUR EKOLOGIS DI KABUPATEN REMBANG - Fitri Sari Purnama Arum; Hadi Setyawan; Marsudi Marsudi (Universitas Sebelas Maret Surakarta, 2016)
Planning and designing Beach Recreation Park Pasarbanggi background by public interest Rembang at recreation park compared to other types of recreation, a need for new tourist destinations in Rembang, potential Pasarbanggi Beach, tourist destination development is the development of a tourist attraction Mangrove Forest Pasarbanggi, and reduce the impact of environmental damage Pasarbanggi Beach. The issue of how to apply the concept of ecological design with a focus on the use of ecological materials, energy efficiency, and waste management in buildings and Recreation Park area in an effort to minimize its environmental impact. The objective of this scheme is to acquire the building design and Recreation Park area as a place of education and leisure by applying the concept of Ecological Architecture. Architectural design method with Ecological Architecture approach is a method to be used and applied to the design of the building and neighborhood Taman Rekreasi Pasarbanggi. Then the results are designs Recreation Park with Ecological Architecture approach that is applied to the use of ecological materials such as exposed brick walls, ceiling container scrap wood and exposed concrete floors; energy efficiency in buildings and the area in the form of the use of sky light in the roof of the building, multiply the number of openings with a transparent glass material, the use of a secondary skin to reduce the sunlight; and the management of waste in the form of management and processing of organic waste into compost, and inorganic waste processing to produce handicrafts. Keywords: Ecological Architecture, Energy Efficiency, Recreation Park, Waste Management.